Genotype environment interaction in fractions of dry matter of awn less bread wheats - Zamora Villa, Víctor Manuel; Torres Tapia, María Alejandra; Colín Rico, Modesto (Revista Mexicana de Ciencias Agrícolas, 2021)
Cereals represent an important contribution to the diet of stabled cattle during the winter season, with oats being the most used species, although there are others with forage potential. The production of dry forage and its fractions in twelve awns less wheat genotypes was evaluated, including three commercial witnesses of other species, in order to determine the magnitude of the environment genotype interaction (IGA), as no information is available at the moment. A random complete block design with three repetitions in five test environments was used, sowing at a density of 120 kg ha-1 and doing traditional management of winter cereals. Forage evaluations were conducted between 112 and 118 days after planting. Dry forage of fractions was analyzed using the AMMI model. Of the IGA detected in the production of dry forage, the largest amount appeared in the stems, followed by that of leaves and finally that of spikes. The wheat genotypes G6, G1, G11 and G9 were rated as desirable along with barley as they exhibited good yield and stability. Oats were the least productive and stable. IGA appeared in both the production of total dry forage and its fractions, with the stems showing the greatest interaction. There are awn less wheats that are more desirable than oats for forage production and their fractions, which can be inserted into winter forage production schemes.